2016
DOI: 10.1111/cmi.12672
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic flux of microvesicles modulate parasite-host cell interaction ofTrypanosoma cruziin eukaryotic cells

Abstract: Extracellular vesicles released from pathogens may alter host cell functions. We previously demonstrated the involvement of host cell-derived microvesicles (MVs) during early interaction between Trypanosoma cruzi metacyclic trypomastigote (META) stage and THP-1 cells. Here, we aim to understand the contribution of different parasite stages and their extracellular vesicles in the interaction with host cells. First, we observed that infective host cell-derived trypomastigote (tissue culture-derived trypomastigot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 80 publications
1
67
0
1
Order By: Relevance
“…Several members of this gene family were mainly found in the membrane bound fractions of YuYu-EVs, while most of them were found in the soluble fractions of Y-EVs. Those data are in agreement with previous secretome analysis [37], showing the presence of soluble and membrane bound TS from T. cruzi trypomastigotes [13,38]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several members of this gene family were mainly found in the membrane bound fractions of YuYu-EVs, while most of them were found in the soluble fractions of Y-EVs. Those data are in agreement with previous secretome analysis [37], showing the presence of soluble and membrane bound TS from T. cruzi trypomastigotes [13,38]. …”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that cruzipain activity remains in the supernatant of parasite culture medium after high-speed centrifugation at 100,000 × g [57]. Secretome analyses of other trypanosomatids [13,14,38] such as Trypanosoma brucei, Leishmania donovani, and Leishmania major have shown that a large proportion, if not all of the secreted proteins are released as membrane-bound vesicles [5860], similar to mammalian exosomes. Interestingly, in L. donovani, the composition and number of secreted vesicles seems to be regulated by conditions mimicking infection of host cells [60].…”
Section: Discussionmentioning
confidence: 99%
“…During T. cruzi infection, EVs can be released from parasites or host cells and can be taken up by both parasites and host cells. For instance, Ramirez et al (2017) showed that the integration rate of EVs with THP1 monocyte cells is significantly higher upon release from human tissuecultured trypomastigotes than from insect stage epimastigotes or metacyclic trypomastigotes. If these infected monocyte-derived EVs fuse with other trypomastigotes, they can offer them protection against lysis from the complement system action (Cestari et al, 2012;Ramirez et al, 2017).…”
Section: Evs In Trypanosomatidsmentioning
confidence: 99%
“…For instance, Ramirez et al (2017) showed that the integration rate of EVs with THP1 monocyte cells is significantly higher upon release from human tissuecultured trypomastigotes than from insect stage epimastigotes or metacyclic trypomastigotes. If these infected monocyte-derived EVs fuse with other trypomastigotes, they can offer them protection against lysis from the complement system action (Cestari et al, 2012;Ramirez et al, 2017). Likely, this protection originates after trypomastigotes and immune complexes interact with each other through their EVs (Diaz Lozano et al, 2017).…”
Section: Evs In Trypanosomatidsmentioning
confidence: 99%
“…colleagues [55] showed that culture derived trypomastigotes and metacyclic trypomastigotes induce different levels of MV release from THP-1 cells. They then used Fluorescence Resonance Energy Transfer (FRET) microscopy to show that THP-1-derived microvesicles can fuse with those produced by the parasite.…”
Section: Exosomes In the Protozoan Trypanosoma Cruzimentioning
confidence: 99%